Epigenetics of prenatal stress in humans: the current research landscape - Dieckmann, Linda; Czamara, Darina (Clinical epigenetics, 2024)
Fetal exposure to prenatal stress can have significant consequences on short- and long-term health. Epigenetic mechanisms, especially DNA methylation (DNAm), are a possible process how these adverse environmental events could be biologically embedded. We evaluated candidate gene as well as epigenome-wide association studies associating prenatal stress and DNAm changes in peripheral tissues; however, most of these findings lack robust replication. Prenatal stress-associated epigenetic changes have also been linked to child health including internalizing problems, neurobehavioral outcomes and stress reactivity. Future studies should focus on refined measurement and definition of prenatal stress and its timing, ideally also incorporating genomic as well as longitudinal information. This will provide further opportunities to enhance our understanding of the biological embedding of prenatal stress exposure.